Levistolide A and periplogenin inhibit the growth of gastric cancer cells in vitro and in vivo - Jia Li Guo; Hong Mei Hu; Shao Chin Lee; Ji Zhong Zhao (Exploration of Drug Science)
Aim: In the present study, the natural products levistolide A (LA) and periplogenin (PPG) were studied for their growth inhibitory effects on the development of gastric cancer cells in vitro and, more critically, in vivo, alone or in combination with the therapeutic medication 5-fluorouracil (5-FU). Methods: Methyl thiazolyl tetrazolium (MTT), also known as 3-(4,5-dimethylthiazol-2-yl)-2,5-diphenyl tetrazolium bromide assays were used for the cell viability study. Apoptosis was detected by western blot to detect the cleavage of caspase substrate poly (ADP-ribose) polymerase (PARP) and terminal deoxynucleotidyl transferase-mediated deoxyuridine triphosphate (dUTP) nick-end labelling (TUNEL) assays. The nude mice bearing gastric cancer cells were used for the anti-cancer activity detection of LA and its combinational treatment effect with 5-FU. Results: The results in the present study shown that the two compounds were able to inhibit the viability of the cancer cells in a dose- and time-dependent manner by MTT method. They could trigger apoptosis when used alone, and more potently, in combination with 5-FU detected by TUNEL positivity and the cleavage of caspase substrate PARP. In nude mice bearing gastric cancer cells, injection (i.p.) of LA or PPG alone inhibited the growth of the cancer cells. The treatment using one of the compounds in combination with 5-FU inhibited the cancer cell growth at a higher level than the treatment by a compound alone. Conclusions: LA and PPG could inhibit the growth of the cancer cells, alone or in combination with 5-FU, in vitro and in vivo, suggesting that they are promising investigational drugs for therapeutic development.